'Idiopathic' chronic bilateral subdural haematoma – a separate entity or a missed cause?. (15th November 2011) - Ahmed, Syed Viqar; Bonny, Stephen; Chandra, Sumit
Abstract : A 65-year-old female was admitted with an 8-week history of gradual onset headache. The headache was worse in the morning and on bending forwards. This was associated with 1 week history of vomiting and 1 day history of difficulty in walking. Medical history was unremarkable apart from treated hypothyroidism. There was no history of trauma. Observations and physical examination were entirely normal. Routine blood tests including the ESR and clotting profile were normal. Given the history had red flags for headache, a CT scan was ordered and this showed bilateral subdural haematomas. The patient was referred to the regional neurosurgical centre where the haematomas were evacuated with good recovery. A follow-up MRI brain and spine did not show any source of bleeding.